Desain dan Pengembangan Aplikasi Penjualan Berbasis Website di Float Smoothies Shop Medan - Dwi Citra Tarcilia Br Berutu; Abdul Khaliq; Supiyandi (CV. Hawari, 2025)
The development of information technology is driving digitalization in various sectors, including the culinary business. Medan Float Smoothies still uses a conventional sales system, which creates various obstacles in order recording, stock management, and financial reporting. Therefore, this study aims to design and develop a website-based sales system to improve operational efficiency. The research method used is Research and Development (R&D) with a Software Development Life Cycle (SDLC) Waterfall model approach. The results show that the implementation of the PHP and MySQL-based system has successfully replaced manual processes, improved transaction accuracy, and expanded market reach through the online ordering feature. With this system, customers can easily view products, make transactions, and obtain real-time stock information. The benefits of this research are increased business efficiency, reduced transaction errors, and provided a more practical shopping experience for customers.